(untitled) (Research, Society and Development, 2021)
The teaching-service integration in the health area, in this case, in nursing, provides professionals with a critical and reflective practice, from the perspective of exchanging knowledge between the protagonists. Therefore, the objective of this work was to identify how the teaching-service integration occurs in the undergraduate nursing course from the professors’ perception. Descriptive-exploratory qualitative research. Data collection carried out from semi-structured interviews. Analysis through Bardin’s Content Analysis. Three categories were identified: 1) professors and teaching-service integration; 2) intersection of teaching, service and the community; and 3) relevance of teaching-service integration from the professors’ perspective. The results indicate the need for articulation between the protagonists of the teaching-service integration process, professors understand integration as a collective that needs all members for an effective and meaningful health practice. Another line of research worth pursuing further is to study different spaces and contexts, such as perceptions of the health system users, tutors, nursing students and different areas of the medical field.